2018
DOI: 10.1177/0886260518779074
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Child Sexual Abuse on Social Functioning in Schizophrenia Spectrum Disorders

Abstract: The objective of this study was to explore social functioning in schizophrenic patients who have suffered child sexual abuse (CSA) in comparison with those who have not suffered from it in a Spanish sample of 50 patients with schizophrenia or schizoaffective disorder. The Quality of Life (QOL) Scale, the Childhood Trauma Questionnaire (CTQ-SF), and the NEO Five Factor Inventory (NEO-FFI) were administered in this study. We found a CSA prevalence of 22% in our sample. Results showed that QOL global scores reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…There was some evidence ( n = 3) for a mediation role of depressive symptoms between CM and impaired global social functioning in schizophrenia (Andrianarisoa et al, 2017 ), and occupational functioning in FEP (Ortega et al, 2020 ), as well as emotion processing in PD (Aas et al, 2017 ). There is also evidence ( n = 2) that maladaptive personality traits (Boyette et al, 2014 ; Lopez-Mongay et al, 2021 ) may mediate between CM and social functioning and relations.…”
Section: Resultsmentioning
confidence: 99%
“…There was some evidence ( n = 3) for a mediation role of depressive symptoms between CM and impaired global social functioning in schizophrenia (Andrianarisoa et al, 2017 ), and occupational functioning in FEP (Ortega et al, 2020 ), as well as emotion processing in PD (Aas et al, 2017 ). There is also evidence ( n = 2) that maladaptive personality traits (Boyette et al, 2014 ; Lopez-Mongay et al, 2021 ) may mediate between CM and social functioning and relations.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, other studies have explored the relationship between traumatic childhood experiences and social functioning in schizophrenia and bipolar disorder [3,22-24]. While the high prevalence of childhood trauma has been consistently reported in schizophrenia and bipolar disorder [25-27], the causal relationship between childhood traumatic events and social functioning has been explored recently [2,28,29]. A previous study revealed that early trauma in psychosis patients affected long-term functional outcome, which was mediated by depressive symptoms [28].…”
Section: Introductionmentioning
confidence: 99%
“…It has five sub-scales measuring different dimensions of child abuse: Physical abuse, emotional abuse, sexual abuse, physical neglect, and emotional neglect [18]. Participants with a score ≥8 were considered to have a history of CSA [19]. This questionnaire was translated from English into Iranian Journal of PSYCHIATRY AND CLINICAL PSYCHOLOGY Arabic and back translated into English for linguistic adaptation.…”
Section: Childhood Trauma Questionnaire Short Form (Ctq-sf)mentioning
confidence: 99%